Description of Complementary Feeding Practice and Nutritional Study of Stunted Childern (6 – 24 months) on Wilangan Health Center, Nganjuk District - Ratih Rani Putri; Annas Buanasita; Taufiqurrahman; Riezky Faisal Nugroho (Journal of Nutrition Explorations, 2023)
The prevalence of stunting among toddlers in Nganjuk District is >20%, and it is a nutritional problem in the community. The aim of this research is to determine the description of complementary feeding practices for stunted toddlers (aged 6-24 months) in the Wilangan Sub-district. The research design employed is cross-sectional, where independent and dependent variables are collected at relatively the same time. The study was conducted from November 2022 to May 2023. This is a descriptive study with 28 stunting children as samples using the total sampling method. Data collection of complementary feeding practices was conducted through interviews, while nutritional status by measured height. The study showed less than 50% of infants received exclusive breastfeeding and timely introduction of complementary feeding at 6 months, but more than 60% did not follow the proper principles of complementary feeding between ages 12 - 24 months. As the age increases the inaccuracy of complementary feeding is getting bigger and this affects the occurence of stunting childern. Therefore, its recommended that mothers of toddlers more active in increasing their knowledge about providing appropriate complementary feeding for their children according to their age stages, with the assistance of community health workers and healthcare personnel.